Three-dimensional modeling of a high temperature polymer electrolyte membrane fuel cell at different operation temperatures. (22nd June 2016) - Caglayan, Dilara Gulcin; Sezgin, Berna; Devrim, Yılser; Eroglu, Inci
Abstract: A three-dimensional model for a high temperature polymer electrolyte membrane (PEM) fuel cell having an active area of 25 cm 2 is developed. Triple mixed serpentine flow channel single cell with phosphoric acid doped polybenzimidazole (PBI) membrane is used in the model. Steady-state, isothermal, single phase assumptions are defined for the system. The model is simulated at different temperatures ranging from 100 to 180 °C to investigate the influence of operation temperature on the performance of the cell. It is seen that there is an improvement in the performance of the cell as the operation temperature increases. Experimental data are used to validate the model both for single channel and triple mixed serpentine flow channel. Current density distribution is obtained at different operating voltages. The predicted results show that at high operating voltages the local current density is almost uniform; whereas, decreasing operating voltage causes non-uniformities in the local current density. Highlights: An isothermal 3D model is built for a single HT-PEMFC with an active area of 25 cm 2 . The temperature influence on the cell performance is investigated between 100 and 180 °C. An empirical relation is given for the ionic conductivity temperature dependency of phosphoric acid doped PBI membrane. Single channel and triple mixed serpentine flow channel models are compared with experimental polarization data at 160 °C. Non-uniformities in the local current density increases decreasing operating voltage.